(untitled) (World Economics and Finance Bulletin, 2022)
The study assessed the influence of dates’ productivity and contribution to the GDP, as well as their disadvantage to rising rates of economic expansion. The standard investigation indicated a direct relationship between each of the independent variables (date prices and the average productivity of dates) and the dependent variable, which is consistent with the logic of economic theory (GDP). Because of Iraq’s economic comparative advantage, the study drew many conclusions and recommendations for enhancing date exports